Neural Circuits for Cognitive Appetite Control in Healthy and Obese Individuals: An fMRI Study - Tuulari, Jetro J.; Karlsson, Henry K.; Hirvonen, Jussi; Salminen, Paulina; Nuutila, Pirjo; Nummenmaa, Lauri (PloS one, 2015)
The mere sight of foods may activate the brain's reward circuitry, and humans often experience difficulties in inhibiting urges to eat upon encountering visual food signals. Imbalance between the reward circuit and those supporting inhibitory control may underlie obesity, yet brain circuits supporting volitional control of appetite and their possible dysfunction that can lead to obesity remain poorly specified. Here we delineated the brain basis of volitional appetite control in healthy and obese individuals with functional magnetic resonance imaging (fMRI). Twenty-seven morbidly obese women (mean BMI = 41.4) and fourteen age-matched normal-weight women (mean BMI = 22.6) were scanned with 1.5 Tesla fMRI while viewing food pictures. They were instructed to inhibit their urge to eat the foods, view the stimuli passively or imagine eating the foods. Across all subjects, a frontal cortical control circuit was activated during appetite inhibition versus passive viewing of the foods. Inhibition minus imagined eating (appetite control) activated bilateral precunei and parietal cortices and frontal regions spanning anterior cingulate and superior medial frontal cortices. During appetite control, obese subjects had lower responses in the medial frontal, middle cingulate and dorsal caudate nuclei. Functional connectivity of the control circuit was increased in morbidly obese versus control subjects during appetite control, which might reflect impaired integrative and executive function in obesity.